Kansas Governors - Socolofsky, Homer E. (University Press of Kansas, 1990)
This onestop reference work is a governors' hall of fame-a compendium of information about the 51 men who have held the chief executive post since the opening of the Kansas Territory in 1854.Using both primary and secondary sources, historian Homer Socolofsky sketches a concise biography of each governor and compares their roles in Kansas history. He also provides comparative election and demographic data, as well as suggestions for additional reading.Supplementing the text are 93 historic photographs, including each chief executive's portrait and autograph. Twelve maps and tables depict and compare aspects of the governors' lives, showing occupational background, birthplace, and residence.Kansas Governors brings together in a single volume a far more complete treatment of both territorial and state governors-as well as acting governors-than can be found in other biographical dictionaries. It will be a useful tool for Kansas history buffs, and an essential reference for school and public libraries.